CONCENTRATE SUBSTITUTION WITH MAGGOT WORMS (Hermetia Illucens) ON THE DIGESTION OF NUTRIENTS IN LAYING CHICKENS - S., Wulandari,; Mahardika, I G.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2025)
A study was conducted to investigate the impact of using maggot larvae in feed on the digestive ability of laying hens. This three month research was carried out in two locations, namely Candikusuma Village, Candikusuma District, Pesisir Selatan Regency, and the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University. In this investigation, four treatments with four replications were used in a completely randomized design. The treatments given included control (P0), commercial feed substitution with maggot larvae at 3% (P1), 4% (P2), and 5% (P3). Based on the analysis findings, there was no significant variation in the capacity of the control group and treatment group to digest dry matter, organic matter and crude fiber (P>0.05). Nevertheless, the rate of crude protein digestion varied significantly between treatment groups P1, P2, and P3. These results indicate that the addition of maggot larvae to food up to 5% has no effect on the digestion of dry matter, organic matter, or crude fiber, but administration at a dose of between 3 and 5% can increase the ability of laying hens to digest raw materials proteins.